The role of bone-derived factors in bone and muscle communication - Li, Guobin; Qi, Mingyan; Liang, Shibin (Frontiers in Endocrinology, 2025)
The interaction between bone and muscle was traditionally considered to be mechanical. However, recent insights into the endocrine functions of these two tissues have led to an emerging concept that bone-muscle biochemical crosstalk occurs through soluble factors. In light of the identification of novel bone-derived factors in recent years, more focus has been shifted to the role of bone in this partnership. Primary factors identified include osteocalcin (Ocn), fibroblast growth factor 23 (FGF23), insulin-like growth factor 1 (IGF1), sclerostin (Sost), prostaglandin E2 (PGE2), fibroblast growth factor 9 (FGF9), Wnt3a, and transforming growth factor beta (TGF-β). This review aims to summarize the current knowledge regarding the influence of bone-derived factors on muscle function. A comprehensive understanding of the cellular and molecular mechanisms underlying bone-muscle communication may facilitate the identification of potential therapeutic strategies for the twin diseases of osteoporosis and sarcopenia.